Teaching Arabic Speaking through Concise Daily Expressions: Evidence from Two Indonesian Secondary Schools - Ahmad Harzaqil; Mustahar Ali Wardana (Lughawiyyat: Jurnal Pendidikan Bahasa dan Sastra Arab, 2022)
Concise daily expressions can bridge the gap between learners’ knowledge of Arabic vocabulary and grammar and their ability to communicate orally. This study examined the implementation of Kitāb al-‘Ibārāt al-Yaumiyyah al-Mūjazah in Arabic speaking instruction at Al-Khayriyyah Islamic Institute and Tihamah School in Cirebon, West Java. A qualitative comparative case-study design was employed, with data collected through classroom observations, semi-structured interviews, and document analysis. The data were analysed thematically through coding, categorization, within-case interpretation, and cross-case comparison. The findings revealed that both institutions used the book through explanation, teacher modelling, guided repetition, pronunciation correction, dialogue practice, and contextual speaking activities. Al-Khayriyyah integrated the expressions more systematically into daily Arabic routines, whereas Tihamah extended them through group conversations, speeches, public speaking, and dramatic performances. In both settings, the expressions helped students initiate speech, participate more actively, and develop greater confidence in oral interaction. Their effectiveness, however, depended on teacher mediation, institutional language environments, practice opportunities, learner readiness, time allocation, and supporting resources. Limited instructional time, differences in comprehension, and insufficient supplementary materials were the main constraints. The study concludes that concise daily expressions function most effectively as linguistic scaffolds when learners progress from memorization toward contextual substitution, interaction, and independent communication. The findings contribute a comparative institutional perspective to Arabic speaking pedagogy and highlight the importance of transforming formulaic expressions into flexible communicative resources.